2018
DOI: 10.1111/nph.15390
|View full text |Cite
|
Sign up to set email alerts
|

TWI1 regulates cell‐to‐cell movement of OSH15 to control leaf cell fate

Abstract: Cell pattern formation in plant leaves has attracted much attention from both plant biologists and breeders. However, in rice, the molecular mechanism remains unclear. Here, we describe the isolation and functional characterization of TWISTED-LEAF1 (TWI1), a critical gene involved in the development of the mestome sheath, vascular bundle sheath, interveinal mesophyll and sclerenchyma in rice leaves. Mutant twi1 plants have twisted leaves which might be caused by the compromised development and disordered patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that OsSND3 and OsMYB14 are co-expressed with SCW-related genes in rice [ 30 , 31 ]. TWI1 is an essential factor limiting the movement of OSH15 , which may enable proper programming of cell specification and promote lignin synthesis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that OsSND3 and OsMYB14 are co-expressed with SCW-related genes in rice [ 30 , 31 ]. TWI1 is an essential factor limiting the movement of OSH15 , which may enable proper programming of cell specification and promote lignin synthesis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leaves from rlm1-D and WT plants were collected and fixed in Carnoy’s solution (ethanol/glacial acetic acid = 3/1) overnight. The samples were then treated according to the methods of Sun et al (2020) and observed as previously described ( Cui et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The stem samples were fixed and immersed in paraffin (Sigma) as previously described (Cui et al, 2019). Briefly, WT, sem1-1, sem1-2 and d1 mutant mature leaf samples were cut from a fresh plant and fixed as soon as possible.…”
Section: Histology and Microscopymentioning
confidence: 99%